2018
DOI: 10.1159/000491113
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin Attenuates D-Galactose-Induced Hippocampal Senescence by Improving Long-Term Hippocampal Potentiation, Neurogenesis, and Cognitive Functions

Abstract: Background: Ginseng has been used to improve brain function and increase longevity. However, little is known about the ingredients of ginseng and molecular mechanisms of its anti-brain aging effects. Gintonin is a novel exogenous ginseng-derived lysophosphatidic acid (LPA) receptor ligand; LPA and LPA1 receptors are involved in adult hippocampal neurogenesis. D-galactose (D-gal) is used to induce brain ­aging in animal models because long-term treatment with D-gal facilitates hippocampal aging in experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
(66 reference statements)
2
30
0
Order By: Relevance
“…To show its possible effects against neurodegenerative diseases, gintonin has been used against established models of neurodegeneration. Nam et al analyzed the effects of gintonin against d -galactose-induced neurodegeneration; they showed that gintonin significantly improved the hippocampal LTP, and improved neurogenesis and cognitive performance in mice [ 75 ]. Similarly, in another study, it was suggested that gintonin reduced scopolamine-induced memory dysfunction in mice.…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…To show its possible effects against neurodegenerative diseases, gintonin has been used against established models of neurodegeneration. Nam et al analyzed the effects of gintonin against d -galactose-induced neurodegeneration; they showed that gintonin significantly improved the hippocampal LTP, and improved neurogenesis and cognitive performance in mice [ 75 ]. Similarly, in another study, it was suggested that gintonin reduced scopolamine-induced memory dysfunction in mice.…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…In addition, in an electrophysiological study, d -galactose decreased the long-term potentiation (LTP) amplitude, which is a basic cellular mechanism that underlies learning and memory. 65 Co-administration of gintonin in d -galactose mice enhanced LTP and restored cognitive functions compared with those in mice treated with d -galactose alone. The LPA and LPA1 receptors play a crucial role in early brain development.…”
Section: Characteristics Of the Lipid Components Of Gintonin And Gefmentioning
confidence: 91%
“…Interestingly, hippocampal LPA1 receptor expression is also diminished under d -galactose insult. 65 Co-administration of gintonin with d -galactose reverses d -galactose-induced reduction of cell proliferation, increases differentiation of immature neurons into mature neurons, and increases LPA1 receptor expression in the mouse hippocampus. Gintonin also increases the expression of phosphorylated cyclic adenosine monophosphate response element binding protein (pCREB), which plays an important role in cognitive functions.…”
Section: Characteristics Of the Lipid Components Of Gintonin And Gefmentioning
confidence: 98%
See 1 more Smart Citation
“…Tau phosphorylation is one of the two hallmarks of AD. D-gal was reported to induce tau hyperphosphorylation in rats [43,44] and impact synaptic plasticity [45], so the expression levels of PHF-1 recognizing tau Ser396/404 were evaluated by Western blot. As shown in Figure 5(d), preventive EA prevented and rescued the tau hyperphosphorylation (P < 0.01).…”
Section: Preventive Electroacupuncture Decreased Tau Hyperphosphorylamentioning
confidence: 99%